Aspen plus : chemical engineering applications - Al-Malah, Kamal I. M. (John Wiley & Sons Inc., 2017)
With step-by-step examples and succinct explanations, this comprehensive book constitutes a running tutorial and provides explanations of need-to-know aspects of Aspen Plus without overwhelming details and cumbersome Aspen Plus features. --